A Review of Moringa oleifera on Physical and Mental Health Effects for Its Nutritional and Therapeutic Potential - Nahar, Shamsun; Ara, Nazma; Faisal, Ferdous Mahmud; Rahman, Tanjila; Saha, Shimu (Journal of Dhaka National Medical College & Hospital, 2014)
Moringa oleifera Lam (Moringaceae) is a highly valued plant, distributed in many countries of the tropics and subtropics. It has an impressive range of medicinal uses with high nutritional value. Different parts of this plant contain a profile of important minerals, and are a good source of protein, vitamins, β-carotene, amino acids and various phenolics. The Moringa plant provides a rich and rare combination of zeatin, quercetin, β-sitosterol, caffeoylquinic acid and kaempferol. In addition to its compelling water purifying powers and high nutritional value, M. oleifera is very important for its medicinal value. Various parts of this plant such as the leaves, roots, seed, bark, fruit, flowers and immature pods act as cardiac and circulatory stimulants, possess antitumor, antipyretic, antiepileptic, antiinflammatory, antiulcer, antispasmodic, diuretic, antihypertensive, cholesterol lowering, antioxidant, antidiabetic, hepatoprotective, antibacterial and antifungal activities, and are being employed for the treatment of different ailments in the indigenous system of medicine, particularly in South Asia. In addition to this, it helps to improve mood maintaing sound health due to its constituent tryptophan–an amino acid. This review focuses on the detailed phytochemical composition, medicinal uses, along with pharmacological properties of different parts of this multipurpose tree. J.Dhaka National Med. Coll. Hos. 2014;20(01):58-63